Dynamic Changes of DNA Methylation and Transcriptome Expression in Porcine Ovaries during Aging. (30th October 2019) - Xi, Xiaoyu; Zou, Qin; Wei, Yingying; Chen, Yan; Wang, Xue; Lv, Daojun; Li, Peilin; Wen, Anxiang; Zhu, Li; Tang, Guoqing; Ma, Jideng; Li, Mingzhou; et al.
Abstract : The biological function of human ovaries declines along with aging. To identify the underlying molecular changes during ovarian aging, pigs were used as model animals. Genome-wide DNA methylation and transcriptome-wide RNA expression analyses were performed via high-throughput sequencing of ovaries from young pigs (180 days, puberty stage of first ovulation) and old pigs (eight years, reproductive exhaustion stage). The results identified 422 different methylation regions between old and young pigs; furthermore, a total of 2, 243 mRNAs, 95 microRNAs, 248 long noncoding RNAs (lncRNAs), and 116 circular RNAs (circRNAs) were differentially expressed during both developmental stages. Gene ontology analysis showed that these genes related to different methylation and expression are involved in the ovarian aging cycle. Specifically, these are involved in cell apoptosis, death effector domain binding, embryonic development, reproduction and fertilization process, ovarian cumulus expansion, and the ovulation cycle. Multigroup cooperative control relationships were also assessed, and competing endogenous RNA (ceRNA) networks were constructed in the ovarian aging cycle. These data will help to clarify ovary age-associated potential molecular changes in DNA methylation and transcriptional patterns over time.